The Impact of Virtual Reality Simulation Training on Nurses’ Competency in Disaster Management: A Scoping Review - Yodha Pranata; Winara Winara; Vera Susanti; Izzati Adha Pratitis; Inggried Angelica Valentina Wiliyams Peni; Nina Maryam; Sultan Muhammad Wahyu Pamungkas; Yanny Trisyani (Universitas Malahayati, 2026)
ABSTRACT Nurses are pivotal in disaster management. Suboptimal preparedness impairs response, communication, and patient safety. Virtual Reality-based training can enhance clinical skills, readiness, and decision-making, yet logistical and cost challenges persist. This scoping review aims to map evidence on the impact of Virtual Reality Simulation (VRS) in enhancing nurses’ competency in disaster management. The methodology framework utilized in this scoping review followed Arksey and O'Malley's approach. Literature was systematically searched across PubMed, Scopus, and EBSCO using keywords: nurses, Virtual Reality Simulation Training, nurses’ competency, and disaster management. Inclusion criteria required English-language publications. All extracted data were systematically tabulated to facilitate comparative analysis and thematic synthesis. A total of 164 articles were identified, nine studies met the inclusion criteria and were selected for this scoping review. VR training consistently improved nurses’ disaster preparedness, response capabilities, knowledge, and satisfaction compared to traditional methods. Immersive VR enhances practical skills, decision-making, and engagement, despite challenges related to resources, infrastructure, and standardization. VR-based training enhances nurses’ disaster preparedness more effectively than conventional methods. Despite its benefits, the widespread adoption of this approach is hindered by infrastructure, resource demands, and technical limitations in developing realistic simulation environments. Keywords: Disaster Management, Disaster Preparedness, Nurse’s Competency, Simulation Training, Virtual Reality.